2018
DOI: 10.15171/jhp.2018.39
|View full text |Cite
|
Sign up to set email alerts
|

Ginger ameliorates reproductive toxicity of formaldehyde in male mice: Evidences for Bcl-2 and Bax

Abstract: Ginger significantly ameliorates oxidative stress induced by formaldehyde toxicity in male reproductive system, therefore, this herb could be used as a natural source for inventing new drugs to cure male infertility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…In mammals, intratesticular injection of calcium chloride, zinc gluconate, HM, and HS have all been tested for chemical castration [ 3 , 16 , 17 , 29 ]. Animals have been reported to be chemically, surgically and mechanically castrated [ 13 , 59 , 61 ]. Because of the risks and disadvantages of surgical castration, we must now turn to non-invasive chemical methods capable of completely stopping spermatogenesis, androgenesis, and libido.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In mammals, intratesticular injection of calcium chloride, zinc gluconate, HM, and HS have all been tested for chemical castration [ 3 , 16 , 17 , 29 ]. Animals have been reported to be chemically, surgically and mechanically castrated [ 13 , 59 , 61 ]. Because of the risks and disadvantages of surgical castration, we must now turn to non-invasive chemical methods capable of completely stopping spermatogenesis, androgenesis, and libido.…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in sperm count in animals has been found to be associated with subfertility or infertility [ 82 ]. Several studies have shown that sperm survival and PMF integrity are negatively affected by the presence of various chemicals that disrupt membrane integrity resulting in higher ab [ 61 , 79 , 83 , 84 ]. The present study revealed a striking disparity in sperm morphology between the control and treatment cohorts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of these plants have been used since ancient times with no report of side effects [37,38]. These plant not only have low side effects, but also may reduce the toxicity of other agents [39,41]. Therefore, they may have multiple beneficial effects.…”
Section: Discussionmentioning
confidence: 99%